Go forth and tell : the life of Augusta Baker, librarian and master storyteller - McDaniel, Breanna J. (Dial Books for Young Readers, 2024)
"A luminous picture book biography about librarian and storyteller Augusta Baker, the first Black coordinator of children's services at all branches of the New York Public library"--